(untitled) (Bangladesh Medical Journal, 2021)
Skin biopsy for histopathology is the most reliable investigation for diagnosis of skin diseases. The main purpose of skin biopsy is to confirm clinical diagnosis but dermatologists usually looking for the concordance with histopathological report. The aim of the study was to observe the consistency of clinical and histopathological diagnosis of skin diseases. An observational study was conducted on 630 patients that undertaken skin biopsy and that was performed at the Department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University from January 2018 to January 2019. Patients who were advised for biopsy by outpatient and inpatient department and the biopsy was done accordingly was included in the study. Finally the inclusion was confirmed when the histopathological report was available. Demographic information, clinical diagnosis, type of biopsy procedure, types of specimen taken and send for histopathological procedure and the histopathological diagnosis was noted in data collection sheet. Histopathological diagnosis and its correlation with clinical diagnosis was assessed for consistency and it was the main outcome measure of the study. The mean age of patients on whom biopsy was performed was 35.14 ±16.57 years and the age range was 5-82 years. Male patients outnumbered female and the male to female ratio was 1.15: 1. Three types of biopsy were performed among them incisional biopsy was the commonest type (93.5%). In most of the cases collected specimen was skin 94.76%, others type of specimens were mucous membrane 2.6%, nail matrix 1.9% and 0.6% specimen was hair follicle. Among the cases 71.43% was diagnosed clinically. The common clinical diagnosis in which biopsy was done was psoriasis and its types 17.77%, lichen planus and its variants 14.12%, the connective tissue diseases 6.19% and infectious diseases 5.39%. In 79.52% cases histopathological diagnosis was done and 68.22% diagnosis was consistent with the clinical diagnosis. The maximum clinico-pathological concordance was found in vesiculo-bullous disease 93.33%. Then connective tissue diseases 79.48%, vasculitides 75% and lichenoid diseases 73.56%. Skin biopsy is a conclusive tool to overcome diagnostic dilemmas in dermatological diseases. The clinico-pathological concordance is assumed lower than the expectation of dermatologists but the collective efforts of dermatologists and pathologists can improve the capacity of diagnosis of biopsy samples. Bangladesh Med J. 2020 Sept; 49(3) : 29-34